Above- and below-ground species richness of bryophytes in Estonian mires: diversity and differences. (3rd July 2021) - Vellak, Kai; Samson, Tiina; Rikka, Miina; Ingerpuu, Nele
ABSTRACT: Introduction: In temperate zones, the main peat-forming plants are bryophytes, and the restoration capacity of disturbed peatland depends largely on the availability of suitable bryophyte diaspores. We investigated the species richness of bryophytes in the above-ground flora and diaspore bank of three types of mire common in Estonia and northern Europe: ombrotrophic bogs, poor fen and rich fen. Methods: The above-ground flora was recorded and diaspore bank samples were collected from study sites in eastern Estonia representing bog, poor fen and rich fen (three sites per mire type). For each mire type, the diaspore bank samples from the study sites were blended and placed in a growth chamber for 6 months, and the bryophytes that subsequently emerged were identified. Key results: In total, 54 bryophyte species were found, including six liverworts. Of the three mire types, rich fen had the most species both above and below ground. The number of species in the diaspore bank was lowest in bog (8) and highest in rich fen (27). Three species with conservation value were found: Hamatocaulis vernicosus (in the above-ground flora only) and Meesia longiseta and Splachnum ampullaceum (in the diaspore bank only). The species richness of the bryophyte diaspore bank was similar and significantly related to that of the above-ground bryophyte flora. Conclusion: In temperate-zone mires, the diaspore bank can be a depository of species that have disappeared from the above-ground flora. The local diaspore bank could a valuable source of species richness for the restoration of disturbed mire communities.